Historical Background of Wang Yang-ming's Philosophy of Mind From the Perspective of his Life Story - Dong, Ping (Springer Nature Singapore : Imprint: Springer, 2020)
This open access book offers comprehensive information on Wang Yang-ming's life, helping readers identify and grasp the foundations on which his philosophy was established. Though a great man, Wang had an extremely difficult life, full of many hardships. Based on various official histories, Wang's own writings, and his disciples' records, the book explores the legendary life of this ancient philosopher, who not only diligently pursued his objective of living as a sage, but also persistently sought the ideal state of a sage in ideology. The author also shares his own interpretations of the main aspects of Wang's philosophy using simple and straightforward language. This book will help readers understand and appreciate Wang Yang-ming's extraordinary life, his generous mind, deep thoughts and bright personality, inspiring them to pursue enriching lives. It offers a unique and insightful work for undergraduate students and all others interested in Wang's philosophy and life story.